LO037: A randomized double-blind trial comparing the effect on pain of an oral sucrose solution versus placebo in children 1 to 3 months old needing urethral catheterization. (2nd June 2016) - Desjardins, M.; Gouin, S.; Gaucher, N.; Lebel, D.; Gravel, J.
Abstract : Introduction: Oral sweet solutions have been accepted as effective analgesics for procedures in the neonatal population. However, there have been a limited number of trials in older infants. These studies have conflicting results. The objective of the study was to compare the efficacy of an oral sucrose solution versus placebo in reducing pain during urethral catheterization in infants 1 to 3 months old in the Emergency Department (ED).Methods: A randomized, double-blind clinical trial was conducted in a pediatric university-affiliated hospital ED. Infants, 1 to 3 months of age, were recruited and randomly allocated to receive 2 ml of 88% sucrose solution (SUC) or 2 ml of placebo solution (PLA) orally, 2 minutes before planned urethral catheterization. The primary outcome measure was the difference in pain scores as assessed by the Face, Legs, Activity, Cry and Consolability (FLACC) Pain Scale at 1 min post procedure. Secondary outcome measures were the difference in pain scores using the Neonatal Infant Pain Scale (NIPS), crying time and variations in heart rate.Results: Seventy-six participants were recruited and completed the study, 37 (group SUC) and 39 (group PLA) respectively. The mean difference in FLACC scores compared to baseline was 5.62 ± 1.32 (SUC) vs. 6.21 ± 1.15 (PLA) (p=.51) during catheterization, 2.70 ± 1.21 (SUC) vs. 2.26 ± 1.41 (PLA) at 1 min (p=.64) and 0.66 ± 1.32 (SUC) vs. 1.26 ± 1.00 (PLA) at 3 mins (p=.38). For the NIPS scores, it was 4.27 ± 1.06 (SUC) vs. 4.69 ± 0.92 (PLA) (p=.56) during procedure, 2.05 ± 0.91 (SUC) vs. 1.97 ± 1.19 (PLA) (p=.92) at 1 min and 0.49 ± 0.89 (SUC) vs. 0.89 ± 0.97 (PLA) (p=.54) at 3 mins. The difference in the mean crying time was not different between both groups: 99 ± 34 secs (SUC) vs. 100 ± 25 (PLA) (p=.99). No significant difference was found in participants' heart rate variations during procedure 23 ± 8 BPM (SUC) vs. 26 ± 7 (PLA) (p=.60), after 1 min 19 ± 12 BPM (SUC) vs. 17 ± 7 (PLA) (p=.76) and after 3 mins -1 ± 12 BPM (SUC) vs. 3 ± 6 (PLA) (p=.53).Conclusion: In infants 1 to 3 months of age undergoing urethral catheterization in the ED, administration of an oral sweet solution did not statistically decrease pain scores as measured by the FLACC and NIPS scales. Participants' heart rate variations and crying time were not significantly decreased when sucrose was provided.